2011
DOI: 10.1038/ajh.2011.5
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Large and Small Artery Elasticity in Healthy Subjects From 9 to 89 Years Old

Abstract: Background We identified demographic variables, cardiovascular risk factors, and ambulatory activity measures that predict large and small artery elasticity in apparently healthy subjects between 9 and 89 years of age. Methods 480 subjects were assessed on large artery elasticity index (LAEI), small artery elasticity index (SAEI), demographic measures, cardiovascular risk factors, and daily ambulation during seven consecutive days. All possible regression and Mallow's Cp were used to select multivariate mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The current observation that large and small arterial elasticity increase with age from 8 to 30 years, particularly in the Caucasians, supports previous reports from our laboratory, 29, 38 and from another laboratory utilizing the same methodology of diastolic pulse contour analysis. 39 We previously found that in subjects completely free of cardiovascular risk factors, large and small arterial elasticity increased with age in children, adolescents, and young adults up to age 30, and declined thereafter, particularly after 50 years of age.…”
Section: Discussionsupporting
confidence: 91%
“…The current observation that large and small arterial elasticity increase with age from 8 to 30 years, particularly in the Caucasians, supports previous reports from our laboratory, 29, 38 and from another laboratory utilizing the same methodology of diastolic pulse contour analysis. 39 We previously found that in subjects completely free of cardiovascular risk factors, large and small arterial elasticity increased with age in children, adolescents, and young adults up to age 30, and declined thereafter, particularly after 50 years of age.…”
Section: Discussionsupporting
confidence: 91%
“…(5, 16, 17) The purposes of this study are (1) to compare daily ambulatory measures in children, adolescents, and young adults with and without metabolic syndrome, and (2) to assess which metabolic syndrome components, demographic measures, and body composition measures are associated with daily ambulatory measures. We hypothesize that objectively measured daily ambulatory cadences are lower in subjects with metabolic syndrome, particularly in those with higher values of body fat percentage.…”
Section: Introductionmentioning
confidence: 99%
“…R2 and R1 were almost identical in the total population, but in participants who were of older age and had hypertension and diabetes, mean R2 exceeded R1. The mechanism of divergence in SBP pattern according to these 3 characteristics is unknown, but may be linked to the decreased large artery compliance that is common to all 3 conditions 36,37 . Older age independently predicted having SBP increase from R1 to R2, a phenomenon observed in 43% of our study population.…”
Section: Discussionmentioning
confidence: 76%